Pengaruh Kualitas Produk, Brand Image dan Desain Produk Terhadap Keputusan Pembelian Iphone: Studi Kasus Pada Pelanggan Toko Fdstore Kota Tebing Tinggi - Suwadi, Suwadi; Nainggolan, Benhard (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This research aims to determine the influence of product quality, brand image and product design on iPhone purchasing decisions (case study of customers of the Fdstore store in Tebing Tinggi City). The research method used is the Quantitative Method using SPSS version 25.00. The technique for determining the sample size used sampling. The total number was 56 respondents, namely consumers who bought iPhones at the Fdstore, Tebing Tinggi City. The sampling technique for this research uses Accidental Sampling. The analytical method used in this research is Multiple Linear Regression Analysis and Hypothesis Testing. The results of this research are 1) Product Quality influences Purchasing Decisions, 2) Brand Image influences Purchasing Decisions, 3) Product Design influences Purchasing Decisions, 4) Product Quality, Brand Image and Product Design simultaneously influence Purchasing Decisions.